Non-infectious Complications of Common Variable Immunodeficiency: Updated Clinical Spectrum, Sequelae, and Insights to Pathogenesis - Ho, Hsi-en; Cunningham-Rundles, Charlotte (Frontiers in Immunology, 2020)
Non-infectious complications in common variable immunodeficiency (CVID) have emerged as a major clinical challenge. Detailed clinical spectrum, organ-specific pathologies and associated sequelae from 623 CVID patients followed in New York since 1974 were analyzed, and recent insights to pathogenesis were reviewed. Non-infectious manifestations were present in 68.1% of patients, and they do not tend to be present in isolation. They include autoimmunity (33.2%), chronic lung disease (30.3%), lymphoid hyperplasia/splenomegaly (20.9%), liver disease (12.7%), granulomas (9.3%), gastrointestinal disease (7.3%), lymphoma (6.7%), and other malignancies (6.4%). In the lungs, interstitial disease and bronchiectasis were the most common findings, with lymphoma at this site being a rare (n = 6), but serious, manifestation. Bronchiectasis was not a prerequisite for the development of interstitial disease. In the liver, granulomas and nodular regenerative hyperplasia were the most common. Gastrointestinal disease may affect any segment of the intestinal tract, with lymphoid infiltrations and villous blunting being the leading histologic findings. With progression of organ-specific diseases, a wide spectrum of associated sequelae was observed. Lymphoma was more common in females (P = 0.036)—all B cell types except in one subject. Solid organ transplantations (liver, n = 5; lung, n = 4; combined lung and heart, n = 2) and hematopoietic stem cell transplantations (for B cell lymphoma, n = 1) have rarely been performed in this cohort, with mixed outcomes. Recent identification of monogenic defects, in 10–30% of various CVID cohorts, has highlighted the molecular pathways that can affect both antibody production and broader immune regulation. In addition, cellular defects in both innate and adaptive immune systems are increasingly recognized in this syndrome.